2012
DOI: 10.1016/s2225-4110(16)30087-6
|View full text |Cite
|
Sign up to set email alerts
|

The Antidiabetic Effect of Garlic Oil is Associated with Ameliorated Oxidative Stress but Not Ameliorated Level of Pro-inflammatory Cytokines in Skeletal Muscle of Streptozotocin-induced Diabetic Rats

Abstract: Oxidative stress and inflammatory condition has been broadly accepted being associated with the progression of diabetes. On the other hand, garlic (大蒜 dà suàn, bulb of Allium sativum) has been shown to possess both antioxidant and anti-inflammatory action in several clinical conditions. Our previous study demonstrated that treatment with garlic oil improves oral glucose tolerance and insulin tolerance and improves the insulin-stimulated utilization of glucose to synthesize glycogen in skeletal muscle in strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 48 publications
2
23
0
2
Order By: Relevance
“…Liu et al found an hypoglycemic effect of garlic oil, associated with a lowered level of NO in skeletal muscle [ 70 ], which is consistent with the finding of another study showing that, in diet-induced metabolic syndromes in rats, treatment with raw garlic homogenate efficiently improves insulin sensitivity and normalizes serum levels of nitric oxide [ 71 ]. These hypoglycemic effects of garlic products might be explained partially by inhibition of proinflammatory mediators.…”
Section: Garlic Preparation Biological Activitiessupporting
confidence: 73%
See 1 more Smart Citation
“…Liu et al found an hypoglycemic effect of garlic oil, associated with a lowered level of NO in skeletal muscle [ 70 ], which is consistent with the finding of another study showing that, in diet-induced metabolic syndromes in rats, treatment with raw garlic homogenate efficiently improves insulin sensitivity and normalizes serum levels of nitric oxide [ 71 ]. These hypoglycemic effects of garlic products might be explained partially by inhibition of proinflammatory mediators.…”
Section: Garlic Preparation Biological Activitiessupporting
confidence: 73%
“…These hypoglycemic effects of garlic products might be explained partially by inhibition of proinflammatory mediators. In fact, inflammation could trigger insulin resistance, and the identified inflammatory factors involved in this process include molecules such as TNF- α , IL-1 β , and NO [ 70 , 72 , 73 ].…”
Section: Garlic Preparation Biological Activitiesmentioning
confidence: 99%
“…The hypoglycemic activity of garlic oil has shown to improve GLUT4 expression in STZ induced diabetic rats. 38 The ethanol extract of Symplocos cochinchinesis bark has also shown to have effects in regulating insulin resistance. The oral administration of S. cochinchinesis extract at 250 and 500 mg kg −1 .day −1 significantly reduced the plasma glucose level in diabetic induced rats with insulin resistant on day 20.…”
Section: Herbal Remedy In Diabetesmentioning
confidence: 99%
“…The significant increase in the level of kidney GSH as well as significant and non-significant decrease in CAT and GPx activities respectively following CHCl 3 administration is an indication of free radical generation (H 2 O 2 ), which the endogenous antioxidant enzymes were responsive to. Antioxidant potentials of DADS was exerted which resulted to the restoration of the renal CAT [63,78e80] and GPx [25,63,81,82] activities.…”
Section: Discussionmentioning
confidence: 99%